2014
DOI: 10.3389/fpsyg.2014.00001
|View full text |Cite
|
Sign up to set email alerts
|

Quality-space theory in olfaction

Abstract: Quality-space theory (QST) explains the nature of the mental qualities distinctive of perceptual states by appeal to their role in perceiving. QST is typically described in terms of the mental qualities that pertain to color. Here we apply QST to the olfactory modalities. Olfaction is in various respects more complex than vision, and so provides a useful test case for QST. To determine whether QST can deal with the challenges olfaction presents, we show how a quality space (QS) could be constructed relying on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

69
908
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 591 publications
(993 citation statements)
references
References 112 publications
(128 reference statements)
69
908
11
Order By: Relevance
“…To enable the conversion of probability scores into z-scores using the in verse phi function, we raised all false alarm rates of 0 to 0.01 and reduced all hit rates of 1 to 0.99 (same method used in Cowan, Naveh-Benjamin, Kilb, & Saults, 2006; Pfeifer, Rothen, Ward, Chan, & Sigala, 2014). We compared sensitivity and criteria between the two traffic load conditions using a paired-sample t-test in both age groups .…”
Section: Resultsmentioning
confidence: 99%
“…To enable the conversion of probability scores into z-scores using the in verse phi function, we raised all false alarm rates of 0 to 0.01 and reduced all hit rates of 1 to 0.99 (same method used in Cowan, Naveh-Benjamin, Kilb, & Saults, 2006; Pfeifer, Rothen, Ward, Chan, & Sigala, 2014). We compared sensitivity and criteria between the two traffic load conditions using a paired-sample t-test in both age groups .…”
Section: Resultsmentioning
confidence: 99%
“…For example, among Stroop tasks, different studies used various categories of words as threatening stimuli, such as adolescent social context words, threatening words, and negative emotion words. Similarly, food images used across studies vary in color, size, palatability, and content, which may introduce error in measurement of AB to food cues (Blechert, Meule, Busch, & Ohla, 2014). One group studying AB has introduced a database of standardized images collected from researchers globally (Blechert, Meule, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that individuals who score highly on measures of grit, and who persevere in the face of difficult tasks, are often more successful in a variety of domains including health, education, and finances [20,22,23,35,36]. It remained unclear whether grittier individuals persist because they believe there are more likely/larger rewards available in the environment than do individuals with less grit, or if instead gritty and non-gritty individuals both make similar inferences regarding what rewards are available in the environment, but gritty individuals infer that they are more likely to actually reach those rewards.…”
Section: Discussionmentioning
confidence: 99%
“…They are also generally more likely to experience greater life success than their less gritty counterparts. For example, individuals high in grit have been shown to have more academic success [19,20], career success [21,22], and overall life satisfaction and happiness [23] as compared to individuals with lower levels of this trait. Grittier individuals are also more likely to successfully complete their training if they are in the military, hold on to their jobs, finish college, and have successful marriages [22] than less gritty individuals.…”
Section: Introductionmentioning
confidence: 99%